2012
DOI: 10.1177/0021943612446732
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Discourse Within a Supply Chain Relationship: Mapping Convergence and Divergence

Abstract: Large organizations involved in supply chain relationships increasingly are creating joint sustainability initiatives. The authors investigated sustainability-related discourse directed to and created by employees representing two organizations engaged in a supply chain relationship. CRAWDAD was used to map the concepts appearing in (a) each company’s sustainability-related training material, and (b) sustainability-focused interviews conducted with employees. Shared terms in the training documents included the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
66
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(66 citation statements)
references
References 57 publications
0
66
0
Order By: Relevance
“…In mature, sustainable NPD processes and organizations, sustainability scope and targets are clear and operational; customized tools, databases, design for sustainability methods, and supply chain tools exist; process definitions include sustainability issues; roles and responsibilities are clear; and NPD designers are experts in sustainability and are active in knowledge networks (Allen et al, 2012). It is imperative that top management develop a cohesive strategy (Alblas et al, 2014) that aligns the firm and its associated supply chains toward delivering sustainable products and services.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In mature, sustainable NPD processes and organizations, sustainability scope and targets are clear and operational; customized tools, databases, design for sustainability methods, and supply chain tools exist; process definitions include sustainability issues; roles and responsibilities are clear; and NPD designers are experts in sustainability and are active in knowledge networks (Allen et al, 2012). It is imperative that top management develop a cohesive strategy (Alblas et al, 2014) that aligns the firm and its associated supply chains toward delivering sustainable products and services.…”
mentioning
confidence: 99%
“…It is imperative that top management develop a cohesive strategy (Alblas et al, 2014) that aligns the firm and its associated supply chains toward delivering sustainable products and services. Corporations that are beginning to address sustainability should focus on what sustainability means for their business and products through defining a sustainability strategy, scope, targets, and processes first, and worry less at the beginning about the metrics (Allen et al, 2012). A recent KPMG global survey showed that roughly two-thirds of companies have a corporate sustainability strategy with a quarter developing one (Sroufe & Melnyk, 2013).…”
mentioning
confidence: 99%
“…There is a also a brief explanation of the criteria used to make the selection in Appendix A, Sections A.1 and A.2, of the supplementary file. Chemical Reaction (10) Christian Aid (11) Corporate Responsibility Coalition (12) Corporate Watch (13) Down to Earth (14) Environmental Investigation Agency (15) Ethical Consumer (16) Friends of the Earth UK (17) Global Witness (18) GreenPeace UK (19) McSpotlight (20) Medact (21) Mines and Communities (22) New Economics Foundation Tag N r. Name of organization and its website (23) Oxfam (24) People and Planet (25) Save the Children UK (26) Tearfund (27) The Corner House (28) The National Trust (29) The Royal Society for the Prevention of Cruelty to Animals (30) The Royal Society for the Protection of Birds (31) The Soil Association (32) The Trade Justice Movement (33) The Woodland Trust (34) War on Want (35) Waste Watch (36) World Development Movement (37) World Wildlife Foundation UK (10) Corus (11) Deloitte Touche (12) ERM Group (13) E-ON UK (14) GlaxoSmith-Kline (15) HSBC holdings plc (16) Land securities (17) Rio Tinto (18) rth group (19) ScottishPower (20) Scottish and Newcastle (21) Severn Trent (22) Shell …”
Section: Methodology/experimental Sectionmentioning
confidence: 99%
“…SSCM in a focal company is largely associated with how the mental models of top managers interpret the internal and external factors affecting their organizations (e.g., environmental and social legislation, internal resources and capabilities, stakeholders concerns, and uncertainty) (Hambrick, 2007;López-Gamero et al, 2011;Sharma, 2000). Top management delivers sustainability policies and provides financial resources to different company divisions and specific projects to motivate workers to apply sustainability practices within the organization and the supply chain; these policies also foster close relationships with suppliers and customers (Allen et al, 2012;Banerjee, 2003;Zutshi and Sohal 2004).…”
Section: Support From Upper and Middle Management For Social And Envimentioning
confidence: 99%